Millennial’s Decision on the Use of Online Halal Marketplace in Indonesia - Muniaty Aisyah (ETIKONOMI, 2023)
This study aims to analyze the Millennials' behavior influenceon their decision to use an online halal marketplace inIndonesia, which is mediated by their perception as anintervening variable. A probability sampling technique withconvenience sampling was used to calculate 100 from 125collected primary data sets. The SEM-PLS statistical techniquewas used to analyze the relationships among variables. Thefindings showed that only technology adoption, opinions,broader activities, and Millennials’ perception influenced theirdecisions to use the online Halal marketplace, while success& status, personal health, and brand value & reward didnot. Millennials’ perception is not an intervening variablefor all indirect effects. It implies that Millennials consideronline Halal marketplace has not been addressed to reservethe Muslim concerns, and their decision to use it didnot necessarily derive from religious reasons. Online Halalmarketplaces must combine more suitable marketing strategiesto increase customer engagement with the Islamic brand byconsistently delivering reliable Halal products and servicesto meet Millennials' needs while penetrating this segment.JEL Classification: M31, M37, L92How to Cite:Aisyah, M. (2023). Millennial’s Decision on the Use of Online Halal Marketplace in Indonesia. Etikonomi, 22(2), 293 – 320. https://doi.org/10.15408/etk.v22i2.34353.